Minimizing seepage in irrigation canals in land reclamation systems via an innovative technology - Kalybekova, Yessenkul; Zhu, Kai; Nurlan, Balgabaev; Seytassanov, Ibragim; Ishangaliyev, Timurlan; Yermek, Auyelbek; Ismailova, Gauharkul; Kurmanbek, Zhanymhan; Issakov, Yerlan; Dávid, Lóránt Dénes (Frontiers in Sustainable Food Systems, 2023)
The escalating demand for water and the impact of climate change are posing significant challenges to global water scarcity and agricultural policies. The aim of this research is to investigate the factors influencing water losses in irrigation systems and provide recommendations to minimize such losses. The research methodology includes conducting studies to identify the factors causing water losses through evaporation and seepage from irrigation canals in the Kazakh part of the Ile River basin. The research results are theoretically substantiated, and a series of field studies are carried out at the inter-farm canal experimental site in Almaty province. Based on the factors affecting evaporation and seepage losses in irrigation canals, a new design of irrigation canal made from geocomposite material has been developed and introduced. This design helps to prevent water losses in inter-farm and on-farm canals of reclamation systems. The geocomposite polymer troughs have improved the technical level of irrigation systems and have enabled additional irrigation areas by increasing the efficiency of irrigation water use in land reclamation systems of Kazakhstan, thereby enhancing the efficiency factor of the irrigation network. Water seepage losses are influenced by several factors, including soil type, canal length, working flow, canal operation mode, canal condition, operation season, and wind impact. Under uniform canal operation mode, water losses are relatively small. However, intermittent modes and incomplete filling of the canal result in increased costs. The research findings indicate that for soils with a flow velocity between 0.10 and 0.30 M/s, water losses due to leakage and evaporation in constant-impact and intermittent-impact channels increase linearly. In intermittent-impact channels, irrigation water losses range from 33.7 to 40.1%. The introduction of geocomposite polymer troughs has the potential to enhance the technical level of irrigation systems by improving the efficiency of the irrigation network and enabling the addition of more irrigation plots. This research aims to reduce water losses in the irrigation canals of reclamation systems, optimize the management of water distribution in irrigation systems, enhance equipment measures, and introduce digital irrigation water metering technologies. Future studies propose the application of digital technologies to enhance irrigation water design and accounting as part of measures to minimize water losses in irrigation canals.